Pengaruh Terapi Birth Ball pada Ibu In-Partu terhadap Intensitas Nyeri Persalinan Kala I Fase Aktif di PMB Nuriman Rafida Jambi - Maria Ulfah; Rosmaria Rosmaria (NHM PRESS, 2021)
Each In-Partu mother can experience pain. In-partu pain can cause delays in the progress of labor which can harm the fetus. Birth Ball is a therapy that can help reduce pain. This study aims to analyze the effect of birth ball therapy on in-partum mothers' intensity of labor pain in the first stage of the active phase. This pre-experimental study used a one-group pre-post-test approach. This study was conducted at PMB Nuriman Rafida Jambi City in the period May-June 2021. This study involved 40 respondents of In-partum mothers in the first active phase who were taken accidentally. Data analysis using t-test. The results showed a decrease in pain intensity between pre-test and post-test with a mean difference of 1.08 with a p-value = 0.000, meaning an effect of pain intensity before and after birth ball therapy was applied.